Using Data to Make Evidence Informed Decisions in School Social Work - Robert Lucio; Michael Campbell; Tiffany Nelson; Courtney Wiest (International Journal of School Social Work, 2024)
Effectively supporting school social workers (SSW) in using data to make evidence informed decisions can be challenging for many reasons. This study examines how SSW utilize data across each step of the data engagement framework and, explores the confidence level of SSW in identifying data as well as specific types of data being utilized in the school setting. Data were collected though mixed-methods survey items with social workers in one district in central Florida asking about the different ways in which SSW were engaged with data usage. Results from the study indicate that SSW felt more comfortable in identifying interventions and their ability to intervene than having the right data, making meaning of data, or evaluating the impact of their interventions. These themes were further explored using the qualitative items which identified specific aspects of data engagement including identification of the right data, accessing data, interpreting results, deciding interventions, monitoring implementation and how SSW learn about interventions.
Keywords: School Social Work; Data Informed Decision Making; School Interventions